Learning Mathematics Through Ethnomatematics Studies Containing Character Values and Cognitive Aspects in Congklak Games for Children of the Dayak Losarang Tribe - Mellawaty Mellawaty; Yohanes Leonardus Sukestiyarno; Isnarto Isnarto; Zaenuri Zaenuri (International Conference on Science, Education, and Technology, 2023)
Technological progress is becoming more advanced and sophisticated, which has both beneficial and bad effects on child development. Children are more interested in modern technology than conventional things, which causes them to develop apathetic and individualistic dispositions. Traditional games are games that are passed down from generation to generation, highlight noble values, cultural values, and character values, and are good for children's development. The purpose of this study was to identify the cognitive elements, character values, and ethnomathematics components of the game of congklak played by children of the Losarang Dayak tribe in relation to learning mathematics. Thus, the congklak game is increasingly popular and is often used in elementary schools to teach mathematics in Indramayu district. This study used an ethnographic design, field notes, conducted in-depth interviews, and made observations to collect data for research. While ethnomodeling is used to represent ideas and mathematical practices of the Losarang Dayak community through ethical, emic, and dialectical approaches in school mathematics, ethno-mathematics as a type of research seeks to uncover the universally significant features of mathematical activity. The congklak game played by Losarang Dayak children has ethnomathematics elements, character values, and cognitive aspects, according to research findings. Playing congklak helps children of the Losarang Dayak Tribe develop social skills, perseverance, thoroughness, and honesty. Besides that, it also increases sportsmanship, develops analytical skills, fosters creativity in children, trains self-development, and sharpens emotional skills. The cognitive skills needed in congklak games include the ability to count, add numbers, develop strategies, improve memory, foster creativity, solve problems, and understand comparisons of many and few.